First update of the International Xenotransplantation Association consensus statement on conditions for undertaking clinical trials of porcine islet products in type 1 diabetes—Chapter 4: pre‐clinical efficacy and complication data required to justify a clinical trial. (25th February 2016) - Cooper, David K.C.; Bottino, Rita; Gianello, Pierre; Graham, Melanie; Hawthorne, Wayne J.; Kirk, Allan D.; Korsgren, Olle; Park, Chung‐Gyu; Weber, Collin
Abstract: In 2009, the International Xenotransplantation Association (IXA) published a consensus document that provided guidelines and "recommendations" ( not regulations) for those contemplating clinical trials of porcine islet transplantation. These guidelines included the IXA's opinion on what constituted "rigorous pre‐clinical studies using the most relevant animal models" and were based on "non‐human primate testing." We now report our discussion following a careful review of the 2009 guidelines as they relate to pre‐clinical testing. In summary, we do not believe there is a need to greatly modify the conclusions and recommendations of the original consensus document. Pre‐clinical studies should be sufficiently rigorous to provide optimism that a clinical trial is likely to be safe and has a realistic chance of success, but need not be so demanding that success might only be achieved by very prolonged experimentation, as this would not be in the interests of patients whose quality of life might benefit immensely from a successful islet xenotransplant. We believe these guidelines will be of benefit to both investigators planning a clinical trial and to institutions and regulatory authorities considering a proposal for a clinical trial. In addition, we suggest consideration should be given to establishing an IXA Clinical Trial Advisory Committee that would be available to advise (but not regulate) researchers considering initiating a clinical trial of xenotransplantation.